Repeatability and Reproducibility of Peripapillary Choroidal Thickness Using a Medical Image-Processing Software - Simoes, Pedro; Silva, Pedro; Cordeiro, Miguel; Costa, Joao (Medical hypothesis, discovery and innovation in ophthalmology, 2018)
Although choroid has been shown to have a vital role in the pathophysiology of many ocular diseases, its role in the pathogenesis of several other conditions remains uncertain. The authors propose a novel methodology to establish a more accurate Peripapillary Choroidal Thickness (PPCT), using an image-processing software. This study sought to evaluate the reproducibility and repeatability of PPCT evaluation with ImageJ software in healthy volunteers. Forty-eight eyes of 24 volunteers were subjected to PPCT area determination, after imaging acquisition and recording with Spectral-domain Optical Coherence Tomography (SD-OCT) Heidelberg Spectralis®, during two different sessions, by two blinded assessors. The age of the subjects was 29.2 ± 4.5 years (mean ± SD). The Coefﬁcient of Repeatability (CR) average measurements of PPCT area was 17.06 mm and 9.48 mm correspondingly, for the ﬁrst and second examiners. Intra-class Correlation Coefﬁcient (ICC) was 0.994 (95% CI 0.989 to 0.997) and 0.998 (95% CI 0.997 to 0.999). Inter-observer Concordance Correlation Coefﬁcient (CCC) was 0.998 (95% CI 0.996 to 0.999) for both examiners. Intra-observer CCC ranged from 0.997 (95% CI 0.996 to 0.999) to 0.998 (95% CI 0.997 to 0.999), correspondingly, for the first and second examiners. The PPCT quantification by means of the proposed methodology showed good inter- and intra-observer agreement for both operators, indicating feasibility and good reproducibility of the proposed methodology. This approach might be used in different clinical settings and potentially contributes to elucidation of the choroid role in ocular pathology.